Islamic Commercial Bank Customer Loyalty with Customer Satisfaction as An Intervening Variable (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
This study sought to examine and evaluate the elements that affect customer loyalty in Islamic commercial Banks, using a quantitative associative method and intervened by customer satisfaction variable. The distribution of survey questions was utilized to collect data. SEM PLS ver.3 Software is used to process and analyze the data. According to the findings, customer loyalty was influenced by brand equity and customer satisfaction. However, customer loyalty was not influencing customers among ICBs. Theoretically, this study implies that banking awards and client pride make it easier for consumers and potential customers to learn about the quality of ICBs’ products and services and trust them. It indicates that the public believes the services offered by ICBs to be of average quality, falling short of excellence. Therefore, ICBs must increase banking awards and client pride to make it easier for clients and prospective consumers to recognize and trust the quality and services.